Fatty acid methyl ester production from wet microalgal biomass by lipase-catalyzed direct transesterification. (October 2016) - Navarro López, Elvira; Robles Medina, Alfonso; Esteban Cerdán, Luis; González Moreno, Pedro A.; Macías Sánchez, María D.; Molina Grima, Emilio
Abstract: The aim of this work was to optimize the production of fatty acid methyl ester (FAME, biodiesel) from wet Nannchloropsis gaditana microalgal biomass by direct enzymatic transesterification. This was done in order to avoid the high cost associated with the prior steps of drying and oil extraction. Saponifiable lipids (SLs) from microalgal biomass were transformed to FAME using the lipase Novozyme 435 (N435) from Candida antarctica as the catalyst, and finally the FAME were extracted with hexane. t-Butanol was used as the reaction medium so as to decrease lipase deactivation and increase mass transfer velocity. A FAME conversion of 99.5% was achieved using wet microalgal biomass homogenized at 140 MPa to enhance cell disruption, a N435:oil mass ratio of 0.32, methanol added in 3 stages to achieve a total of 4.6 cm 3  g −1 of oil and 7.1 cm 3  g −1 oil of added t-butanol, with a reaction time of 56 h. The FAME conversion decreased to 57% after catalyzing three reactions with the same lipase batch. This work shows the influence of the polar lipids contained in the microalgal biomass both on the reaction velocity and on lipase activity. Highlights: Microalgal lipids transformed into biodiesel without drying or prior extraction. Lipids were transformed to FAME by lipase catalyzed direct transesterification. The importance of polar lipids for FAME conversion is showed. Influence of t-butanol:oil ratio and polar lipids on lipase stability is discussed. 99.5% of microalgal saponifiable lipids were transformed to FAME.